Impediments to teaching the second generation curriculum from the point of view of primary teachers in Algeria - Ben amour, jamila; Belahdji , Fouzia; Khaira, Chaib (Journal of Curriculum and Teaching Methodology, 2022)
The current study aimed to reveal the obstacles to teaching second generation curricula from the viewpoint of primary education teachers on a sample of (84) primary education teachers in Chlef) Algeria) schools using both the descriptive approach, and the measure of obstacles to teaching second generation curricula that was completed in the current study; The statistical analysis of the study data resulted in the following results: The most common obstacles related to teaching the second generation curricula are the obstacles related to the lesson implementation dimension by 32.41%, the obstacles related to the lesson planning dimension by 25.76%, the obstacles related to the training dimension by 21.85%, then the obstacles related to the lesson evaluation dimension for 20%, and the results of the study showed that there were no statistically significant differences in teaching obstacles due to each of the gender variable (male, female), and the educational qualification variable (Bachelor, Master, graduates of the Higher School of Teachers, graduates of the Technological Institute of Education). and the experience variable (less than 5 years, from 5 to 10 years, more than 10 years), while the differences were significant in relation to the university specialization variable (literary, scientific, languages) in favor of languages ​​specialization, and in light of these results, a number of recommendations and suggestions were presented The most important of these is the involvement of professors and specialists with competence and professional experience in preparing curricula and courses.